Application of Blockchain Technology for Innovation in the Education Sector - Shalim, Nazir (Enigma Institute, 2023)
The utilization of blockchain technology holds immense potential to profoundly influence the field of education in the forthcoming years. This technology has the potential to enhance the security, transparency, and affordability of education. Blockchain technology can be employed to securely and permanently maintain student education records. Implementing this can enable students to monitor their academic advancement and receive acknowledgement for their accomplishments. Employing blockchain technology can issue educational certificates that possess a high level of security and are impervious to counterfeiting. This might facilitate students in securing employment or pursuing further education at an advanced level. The implementation of blockchain technology can enhance the security and dependability of online learning platforms. One way to achieve this is by using blockchain technology to store educational resources, evaluations, and communication between students and educators. Blockchain technology can facilitate the creation of adaptive learning systems that have the ability to customize learning materials and procedures according to the individual requirements of each learner. Blockchain technology has the potential to establish a learning environment that is decentralized and characterized by increased democratic participation. A collective or network comprising diverse stakeholders, including students, educators, and parents, typically oversees this educational setting.